Reflections on Village Autonomy through the Implementation of Village Funds in Gampong Kapa, East Langsa District, Langsa City - Muklir Muklir; Fadhil Fadhil (FISIP Universitas Malikussaleh, 2021)
Village funds are provided by the central government to villages (gampong) to improve the welfare of the gampong community. The existence of village funds is expected to increase community productivity. This study aims to explain how the implementation of village fund policies in Gampong Kapa in 2019 by linking the policy implementation model according to Grindle. The research method used is descriptive qualitative. Data collection was carried out through interviews, observation, and documentation. The results showed that the implementation of village fund policies in Gampong Kapa has not been carried out well even though the budget absorption has reached 100%. The process is following the existing regulations, but in the implementation in the field, there are many problems. The development and empowerment activities made by the gampong government are not felt by the community. This is because the implementation of village funds in Gampong Kapa does not pay attention to both the policy context and policy content so that the village funds disbursed by the central government in very large numbers are considered by some residents to be not optimal in improving the welfare of the people of Gampong Kapa.